Derailment-resistant performance of modular composite rail track slabs. (1st April 2018) - Kaewunruen, Sakdirat; Wang, Yikai; Ngamkhanong, Chayut
Highlights: Derailment resistant performance of composite track slabs is firstly presented. Full-scale composite track slabs are modelled and validated. Impact capacities of composite track slabs have been identified considering strain rate effect. Strain rate effects play a significant role on the ability of composite track slabs to resist extreme impact events. Numerical simulations without strain-rate effects are relatively more conservative that those with strain rate effects. Abstract: Railway transportation, comprising freight and passenger transport, is the lifeblood of the social economy of a country today, especially for developing countries. Despite over a decade of operations, derailment accidents are among the most frequent accidents for railway transportation and may cause fatally or severe injury to passengers, loss of property and damage to the railway track. Hence, this study focuses predominantly on the structural response and performance evaluation of composite rail track slabs through 3D finite element analysis using ABAQUS. The response and performance of composite track slab subjected to derailment actions has been observed. Material strain-rate properties and impact loads have been introduced to the numerical simulation in order to investigate impact behaviours of composite slabs subjected to derailment loading in explicit dynamic analysis. Based on obtained results, it was found that 45 km/h in the direction of gravity is the limit impact velocity for the designed composite rail track slab. The outcome of this study will improve the design standard and calculation of composite rail track slabs subjected to derailment actions.